2017
DOI: 10.1200/jco.2017.35.15_suppl.e14520
|View full text |Cite
|
Sign up to set email alerts
|

Radiomic biomarkers for the prediction of immunotherapy outcome in patients with metastatic non-small cell lung cancer.

Abstract: e14520 Background: PD-1 checkpoint inhibitors have recently been approved for the treatment of patients with metastatic NSCLC. Predicting to what extent patients will benefit from these treatments is challenging. Research on predictive biomarkers focus on genetic and histological markers from biopsies, necessarily limited to parts of the tumor. Radiomics is a novel approach to quantify characteristics of the tumor on medical imaging, which may have potential value as non-invasive biomarkers. In this study, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Previous studies have also used radiomics to predict response to ICIs (15,24,62,63). Response to immunotherapy was negatively correlated with tumor convexity and positively correlated with edgeto-core size ratio on CT scans of patients with NSCLC (64).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have also used radiomics to predict response to ICIs (15,24,62,63). Response to immunotherapy was negatively correlated with tumor convexity and positively correlated with edgeto-core size ratio on CT scans of patients with NSCLC (64).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, radiomic features in regions around the tumor might reflect immune response in breast and lung cancers (9)(10)(11). In addition to intranodular heterogeneity in PD-L1 status (12)(13)(14)(15), microenvironmental factors in the peritumoral region may be contributing to treatment failure. For instance, angiogenesis, a pathologic response to hypoxia, is routinely observed adjacent to the tumor.…”
Section: Introductionmentioning
confidence: 99%
“…Research on predictive biomarkers is currently focused on genetic and histological markers from biopsies. However, ML and radiomics have shown promising results in improving patient selection and outcome prediction by providing unique insights into tumour and its microenvironment in a noninvasive manner . For example, Charoentong et al used ML algorithms on cancer antigenomes from The Cancer Immunome Atlas to identify determinants of tumour immunogenicity and developed a scoring scheme for predicting response to CPI's, while Coroller et al demonstrated predictive radiomic features for treatment response using CT data .…”
Section: Machine Learning and Immunotherapymentioning
confidence: 99%
“…Radiomics refers to the process of image analysis that results in high-throughput extraction of subvisual and quantitative features from radiologic scans including x-rays, computed tomography (CT), ultrasound, and magnetic resonance imaging. Recently, radiomic approaches have been applied in the context of prognosticating outcome and predicting response to IO (11)(12)(13)(14). Most of these studies have analyzed the tumoral shape and textural radiomic features for predicting response and outcome in patients with NSCLC.…”
Section: Introductionmentioning
confidence: 99%